2023
DOI: 10.1007/s10055-023-00749-4
|View full text |Cite|
|
Sign up to set email alerts
|

Acceptance and use of virtual reality games: an extension of HMSAM

Abstract: Virtual reality (VR) is considered as one of the technological megatrends of 2020s, and today, VR systems are used in various settings, digital gaming being among the most popular ones. However, there has been a dearth of understanding regarding the central factors behind VR gaming acceptance and use. The present study therefore aimed to explain the factors that drive the use and acceptance of VR games. We extended the hedonic-motivation system acceptance model with utilitarian and inconvenience factors to cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Firstly, Attitude towards its use achieved a remarkable score (6.01/7). The IVR designed with the experiential and situated learning approach (Schott and Marshall 2018) was perceived as challenging and it aroused curiosity, two issues associated with technology acceptance (Cheng 2023;Holden and Rada 2011;Kari and Kosa 2023). In terms of teacher training, these attitudes may foster critical thinking during reflection on practice, thus reinforcing professional learning processes, as it allows pre-service teachers to re-signify the experience and gain greater understanding of their actions (Clarà et al 2019;Seufert et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, Attitude towards its use achieved a remarkable score (6.01/7). The IVR designed with the experiential and situated learning approach (Schott and Marshall 2018) was perceived as challenging and it aroused curiosity, two issues associated with technology acceptance (Cheng 2023;Holden and Rada 2011;Kari and Kosa 2023). In terms of teacher training, these attitudes may foster critical thinking during reflection on practice, thus reinforcing professional learning processes, as it allows pre-service teachers to re-signify the experience and gain greater understanding of their actions (Clarà et al 2019;Seufert et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…To optimise the effectiveness of deploying learning content, Sander (2010) underscores the criticality of usability testing. This practice enables developers, trainers, and end users to grasp interaction dynamics and identify usability issues (Holden and Rada 2011;Kari and Kosa 2023). Given the contextual dependency of 'magic number' rules for sample sizes in usability testing (Lewis 2014), it is imperative to complement quantitative measures with qualitative methods for assessing instructional design quality (Shernoff et al 2018).…”
Section: Virtual Reality Learning Environment For Teacher Trainingmentioning
confidence: 99%
“…It indicated that ease of use of technology could be instrumental in the usefulness of technology, curiosity for using technology, joy for using it, and control of the technology they are using. Many previous studies have documented that PEOU has a significant influence on PU (e.g., Davis, 1989;Pokhrel, 2022); Curiosity, Joy and Control (e.g., Deng & Yu, 2023;Huda et al, 2020;Kari & Kosa, 2023;Oluwajana et al, 2018). It refers to the ease of using technology that can develop curiosity, joy, and control over using technology such as ChatGPT.…”
Section: Relationship Between Perceived Ease Of Use and Controlmentioning
confidence: 97%
“…It's different from the standard technology acceptance model (TAM) because HMSAM considers a more complex idea of cognitive absorption, which includes things like joy, control, curiosity, focus, and feeling like you're in a different world. Several studies have applied HMSAM to investigate adoption behaviours such as TikTok users in higher education (Deng &Yu, 2023); virtual reality games (Kari & Kosa, 2023); gamified learning environments (Oluwajana et al, 2018)…”
Section: Introduction and Study Objectivesmentioning
confidence: 99%
“…In social experiences, virtual reality can enhance social experiences by bringing users together in virtual worlds. It can support social interactions such as virtual concerts, events and meetings [13].…”
Section: Introductionmentioning
confidence: 99%